(untitled) (KULT_online, 2011)
Ten years after the event, this new study offers a profound narratological analysis of American 9/11 fiction in the fields of literature, television, and movies. It shows how the media take part in reacting to a collective trauma by (re-)constructing different facets of a complex media event and its cultural meaning. A fruitful, balanced contribution to the academic discourse of 9/11.